Arsenic Adsorption performance of lignite in laboratory column experiments under saturated flow conditions - Mar, K.K (ASEAN engineering journal)
This paper presents the adsorption behavior of arsenic (As) onto lignite in saturated column experiments under various flow rates and adsorbent thickness. The lignite sample originated from Indonesia is predominantly composed of organic matter with minor amounts of pyrite (FeS2). Arsenic content of lignite is 1.8 mg/kg with high sulfur content of 10.8 wt. %. The experiments were performed at room temperature using a glass column with an inner diameter of 2.4 cm and total length of 30 cm. Different lignite bed thickness (6 and 12 cm) at a constant flow rate of 0.85 and 0.22 cm³/min and a fixed lignite bed thickness of 12 cm with different flow rates (0.85 and 0.22 cm³/min) were conducted. All effluents had acidic pH (1.04 to 3.36) and were under oxidizing conditions (Eh: +554 - + 629 mV) regardless of the flow rate and lignite bed thickness. The breakthrough of as indicated both leaching and adsorption regions. The leaching of As could be attributed to very high concentration of dissolved organic carbon (DOC) that competes with As for Adsorption sites. Leaching region occurs until ca. 69 mL (ca. 1.35 h) at a thinner lignite bed. After this the concentration of As is the effluent slowly increased and then reached the influent As concentration. In contract, the retardation of As adsorption increased substantially at thicker lignite bed. Decreasing of the flow rate (0.22 cm³/min) had a similar effect with case 2, that is, the As adsorption increased substantially. Based on these results, As removal efficiency under flow-through conditions is strongly influenced by thickness of adsorbent but not the flow rate.